2002
DOI: 10.1055/s-2002-36846
|View full text |Cite
|
Sign up to set email alerts
|

Transumbilical Laparoscopic-Assisted Appendectomy (TULAA): A Safe and Useful Alternative for Uncomplicated Appendicitis

Abstract: TULAA is the best approach in uncomplicated appendicitis. It is less invasive and traumatic, permits a complete evaluation of the peritoneal cavity with superior cosmetic results, especially in obese patients and in cases of ectopic appendicitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
32
0
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 4 publications
1
32
0
4
Order By: Relevance
“…With advances in instrumentation and surgical experience, many laparoscopic surgeons have attempted to minimize the number of ports to reduce traces of the operation, and LSPS was borne of these efforts. Various surgical procedures, including appendectomy, cholecystectomy, and adrenalectomy, have been attempted with LSPS, which presents certain advantages such as minimal scarring, less incisional pain, and the ability to add another trocar to perform multiport surgery [5][6][7][8]. The technique has attracted many laparoscopic surgeons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With advances in instrumentation and surgical experience, many laparoscopic surgeons have attempted to minimize the number of ports to reduce traces of the operation, and LSPS was borne of these efforts. Various surgical procedures, including appendectomy, cholecystectomy, and adrenalectomy, have been attempted with LSPS, which presents certain advantages such as minimal scarring, less incisional pain, and the ability to add another trocar to perform multiport surgery [5][6][7][8]. The technique has attracted many laparoscopic surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…This approach offers better cosmetic results (scarless abdominal surgery via umbilical incision), less incisional pain, and the capability to convert to multiport surgery if required [5][6][7][8]. However, making a ''knot'' when using the LSPS technique was more time-consuming and challenging than when using the conventional multiport laparoscopic technique to treat a perforated duodenal ulcer.…”
mentioning
confidence: 99%
“…Usually a rigid laparoscope with a working channel was used in this technique. The appendix was pulled out through the umbilical port by using a grasper inserted through the channel and removed extracorporeally [10,11]. Cuesta et al [12] recently introduced a transumbilical scarless cholecystectomy technique in ten patients with gallstones.…”
Section: Discussionmentioning
confidence: 99%
“…Although port site infection was 2.5 times higher in the TULAA group (13.7% versus 4.6%), that difference did not reach statistical significance. In TULAA procedures, Koontz et al [12] reported a wound site infection rate of 6.3%, D'Alessio et al [4] 4%, Meyer et al [16] 3.6 %, and Pappalepore et al [19] only 1.5%.…”
Section: Discussionmentioning
confidence: 99%